Lack of evidence of acute HEV infections as a sexually transmitted disease: Data from a German cohort of PrEP users - Guido Schäfer; Rabea Lübke; Olaf Degen; Maria Mader; Robin Scheiter; Annika Wolski; Marylyn M. Addo; Julian Schulze zur Wiesch; Sven Pischke (Brazilian Journal of Infectious Diseases, 2024)
Background: While the sexual transmissibility of HAV in MSM has been extensively described, the potential for sexual transmission of HEV has not been definitively established. Although HEV has been detected in the ejaculate of chronically infected men, studies among MSM PrEP users in France did not observe an elevated anti-HEV seroprevalence as an indicator of increased exposure risk by sexual intercourse. Patients and methods: A total of 111 unselected PrEP users and 111 age- and sex-matched blood donors were tested for anti-HEV IgG, IgM and HEV (PCR). Of the participants 79/111 (71 %) responded to a questionnaire covering topics as sexual preferences, previous sexually transmitted diseases, profession, food consumption, and pet ownership. Results: The anti-HEV IgG seroprevalence in PrEP users (22 %) did not differ significantly from the rate in controls (17 %). While one PrEP user and three controls tested positive for anti-HEV IgM, all PrEP users and controls tested PCR negative. Conclusion: In immunocompetent individuals with frequent changes of sexual partners, the epidemiology of Hepatitis E Virus does not significantly involve the sexual transmission route.